Analysis of the Environmental Quality of Seawater in the Bohai Sea, China - Min Yang; Qian Cheng; Chaozhong Xin; Lijuan Han; Linhao Niu (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
According to the survey data on seawater quality in the Bohai Sea from 2020 to 2021, a single-factor data analysis was carried out on the seawater environmental quality of Liaoning, Hebei, Tianjin, Shandong and the offshore waters. The results show that the seawater quality of the Bohai Sea in 2021 Compared with the more serious pollution in 2020, the main pollutants are active phosphate and inorganic nitrogen. The spatiotemporal distribution characteristics of the eutrophication state index are high at the top of Bohai Bay and low on the outside, high in the southeast and low in the northwest. And through the comparison of water quality data for two years, the organic pollution and eutrophication near Panjin, Dalian, Yingkou and Weifang are getting worse day by day and the content of inorganic nitrogen and active phosphate in some waters in the Bohai Bay has increased. The total amount of materials discharged into the sea is controlled.